Hieracium caesnense (Asteraceae), a new species in H. sect. Villosa from Banat in Romania - Szeląg, Zbigniew (Phytotaxa, 2026)
Hieracium caesnense is a new apomictic, tetraploid (x = 9) species combining the morphological features of H. pilosum and H. lanceolatum. It grows in relict habitats in the Ţăsna Gorge in the Mehedinți Mountains, southern Romania.